Mental Health during the new Coronavirus Pandemic: some necessary reflections (Research, Society and Development, 2020)
The text aims to reflect upon mental health in some specific segments during the new coronavirus pandemic. This is a literature narrative review conducted in the following databases: SciELO and LILACS, using as searching terms health professionals, mental health, mentally ill person, grief, grieving families, pandemic, and COVID-19. Reflection resulted in four topics development: psychological distress and possibilities of getting sick; mental health of health professionals; of mentally ill persons; and of grieving families. We conclude this, suggesting the existence of a real possibility for psychological distress and mental disorders appearance. The population in social isolation and quarantine stands out, as well as health professionals at the front line of combat against COVID-19, people with mental disorders, and grieving families. We understand the new coronavirus pandemic as a contribution to the improvement of mental health practices and for research in crisis situations, emergencies, and great disasters.